Selected Discourses Relating to Non-Muslims: A Review of Madkhali’s Refutation of Sayyid Qutb - Ahmad Arikewuyo, Nafiu (Jurnal Usuluddin, 2024)
The attitude of Islam towards non-Muslims has been a subject of attention for contemporary Muslim scholars as well as the non-Muslim researchers. While the Muslim scholars are interested in presenting the just system adopted by Islam for non-Muslims, some Western scholars are keen on identifying the loopholes inherent in the Islamic system. Of the modern scholars who have contributed to the discourse, with much influence on the contemporary Muslim scholarship, are Sayyid Qutb and Rabi’u Madkhali. The former enjoys much patronage of the Islamists, while the latter is a diehard salafi jurist reputable for his pathological hatred and refutations for the Islamists and modernists. Against this background, this study reviews Madkhali’s refutations of Qutb over selected issues concerning the non-Muslims living under the Muslim rule. The study observes from the three issues discussed in this paper that Madkhali is under the influence of past black pages of the Muslim history when hostility and enmity were the order of the day, while Qutb represents more of the view of modern jurists, who need to face the challenges of modern state. The study recommends further investigation into Madkhali’s other refutations of Sayyid Qutb.